DAMPAK IMPLEMENTASI KEBIJAKAN TARIF CUKAI MINUMAN MENGANDUNG ETIL ALKOHOL DI SULAWESI BAGIAN SELATAN (STUDI PADA KANTOR WILAYAH BEA DAN CUKAI SULBAGSEL) - Besse Jahratunnisa; Nurul Afifah; Mahardian Hersanti Paramita (JURNAL PABEAN : PERPAJAKAN BISNIS EKONOMI AKUNTANSI MANAJEMEN, 2021)
Customs and Excise is a government agency that serves the public in the field of customs and excise. the purpose of this study is to determine the Impact of the Implementation of Excise Tariff Policy for Containing Ethyl Alcohol in Southern Sulawesi. The research method used is qualitative descriptive analysis of data by describing or describing data that has been collected as it is. The results of the study were the decrease in MMEA excise tax receipts due to the decrease in MMEA excise band orders. From 2017 to 2019 it always experiences fluctuations as a result of the existence of local government regulations regarding restrictions on the sale of alcoholic beverages, Sulbagsel Customs and Excise Regional Office always conducts socialization and guidance if there is a new policy from the government. This is strived to optimize services for service users.. Keyword: Customs and Excise, Ethyl Alcohol, MMEA.